Residential doors in the Moroccan Islamic city Through the books of calamities - a documentary study - - benhammou, mohamed; benhammou, Abdul Qadir (The Algerian Historical Journal, 2026)
The article addresses an important architectural issue related to the provisions of the doors (entrances) of dwellings in the Islamic city, which the scholars established and fixed based on the provisions of Islamic law and the fatwas of jurisprudential scholars in general, and based on the catastrophes that occurred in the Islamic city, for which Moroccan scholars devoted special books in which they detailed them and issued their rulings with the help of Construction wizards. We will see that opening doors (entrances) to homes in cities was not spontaneous, but rather was in accordance with controls that sought to preserve the sanctity of the Muslim individual within his home and city.